DEVELOPMENT OF CULTURAL DIVERSITY SUBTHEME TEACHING MATERIALS FOR CLASS IV TO INCREASE THE EFFECTIVENESS OF THEMATIC LEARNING BASED ON LOCAL WISDOM IN BANGKA BARAT - Putri Puspitasari; Amir Hamzah; Tastin Tastin (Department of Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Alauddin Makass, 2022)
Abstract Local wisdom contained in an area is very diverse. One of the local wisdom is found in West Bangka district as the community's identity, which is still being carried out from generation to generation. Thematic learning links various aspects of the student environment. This research aimed to develop cultural diversity learning materials to increase the effectiveness of thematic learning. This research was carried out using the R&D method with ADDIE model. The research subjects involved were 8 students and 3 experts. The instruments used to collect data were questionnaires and documents. The data were analyzed using ADDIE steps: Analysis, Design, Development, Implementation, and Evaluation. The result indicated that the students were very enthusiastic about the developed teaching materials because it was easy to understand and received very good responses from students. The developed teaching materials for class IV received a positive response from students.